Clinical Presentation and Short-Term Prognosis of Faciobrachial Dystonia - Hossain, Redwana; Raknuzzaman, Md; Mia, Md Sajib; Miah, Mohammed Zubayer; Khan, Muhammad Zillur Rahman (Journal of Shaheed Suhrawardy Medical College, 2025)
Wide range of disorders fall into the intersection between Psychiatry and Neurology. Movement Disorders namely dystonia, chorea, tics, tremors and myoclonus often raise dilemma between coarse brain pathology and functional disorder. Faciobrachial Dystonia due to autoimmune encephalitis presents with dystonic movements of face and arm; memory impairment and psychiatric symptoms which may create uncertainty between the diagnosis of neurologic disorder and psychogenic movement disorder. This is a case of a middle-aged lady who presented in the chamber of a psychiatrist with irrelevant speech, jerky movement of right side of face and hand and forgetfulness of recent events. MMSE score at the presentation were 20. Her symptoms were not responsive to conventional anti-epileptic, anxiolytic or sedative-hypnotics. Thus, she was advised an MRI on the basis of which she was referred to a neurologist. On the basis of clinical presentation, physical and mental state examination and laboratory investigation, the lady has been diagnosed as a case of Faciobrachial Dystonia due to anti LGI 1 autoimmune encephalitis. She was given Methyl Prednisolone 1 gm daily for 5 days followed by oral methyl Prednisolone and rapid tapering within 1 month. Following high dose steroid treatment, the frequency of her dystonic movements improved robustly. Psychiatrists are often the first point of contact for the patients with movement disorder. Knowledge and skills for early diagnosis and timely referral makes the care more comprehensive for the patients. Moreover, they can collaborate with neurologists and other healthcare professionals to provide integrated, multidisciplinary care that addresses both the physical and mental health needs of the patients. J Shaheed Suhrawardy Med Coll 2023; 15(2): 44-46